DNA Interaction, DNA Photocleavage, Photocytotoxicity In Vitro, and Molecular Docking of Naphthyl-Appended Ruthenium Complexes - Xia Hu; Qian Luo; Yao Qin; Yao Wu; Xue-Wen Liu (Molecules, 2022)
With the development of metal-based drugs, Ru(II) compounds present potential applications of PDT (photodynamic therapy) and anticancer reagents. We herein synthesized two naphthyl-appended ruthenium complexes by the combination of the ligand with naphthyl and bipyridyl. The DNA affinities, photocleavage abilities, and photocytotoxicity were studied by various spectral methods, viscosity measurement, theoretical computation method, gel electrophoresis, and MTT method. Two complexes exhibited strong interaction with calf thymus DNA by intercalation. Production of singlet oxygen (1O2) led to obvious DNA photocleavage activities of two complexes under 365 nm light. Furthermore, two complexes displayed obvious photocytotoxicity and low dark cytotoxicity towards Hela, A549, and A375 cells.